Labor protest in Costa Rica (2013-2019): actors, repertoires and demands - Alvarado Alcázar, Alejandro (2022)
Through a methodology based on the Protest Event Analysis (pea), the purpose of this work is to investigate the configuration and characteristics of the labor protest in the Costa Rican public sector during the period between 2013 and 2019. It is particularly interested in identify and characterize the behavior of this sector in terms of its actors, repertoires and demands. A discussion related to the defendants is also introduced. The work concludes that, in the case of Costa Rica, public sector labor protest occupies a central place in the general panorama of social protest in the country. Likewise, it postulates that the workers of the public sector resort predominantly to repertoires of institutional action to present their demands, although this trend is modified in periods of intensification of the political contest. Lastly, the demands show a double character inasmuch as the union / sectoral claims related to the defense of labor conditions persist as the main ones, but added to general demands related to campaigns against neoliberal policies and in defense of public institutionality.